PENGARUH MODEL PEMBELAJARAN SAVI BERBASIS MULTIMEDIA TERHADAP MINAT DAN PRESTASI BELAJAR MAHASISWA PADA MATA KULIAH MEDIA PEMBELAJARAN - Hermawan Wahyu Setiadi (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2016)
The aims of this research is to analyze the difference of learning interest and learningachievement subject of media learning between students who followed multimedia based learningSAVI model and students who followed conventional learning model. The Populations in thisresearch were entire students class academic year 2014/2015 amount of 231 students. Samplingtechnique used was random sampling with a sample amount of 90 students. The data of learninginterest were collected using questionnaire and learning achievement subject of media learningwere collected using test. The data were analyzed by using descriptive statistic and MANOVA. Theresearch result shows that: (1) there is difference of learning interest between students whofollowed multimedia based learning SAVI model and students who followed conventional learningmodel in which the value of F19.620 < 0.05, (2) there is difference of learning achievementbetween students who followed learning achievement subject of media learning and students whofollowed conventional learning model in which multivariate test result produces value of F count 32.940< 0.05, (3) there is a difference of learning interest and learning achievement subject ofmedia learning simultaneously between students who followed multimedia based learning SAVImodel and students who followed conventional learning model in which MANOVA test onsignificant level F 28.470 produces value p < 0.05. Key Words: Multimedia based learning SAVI, Learning interest, Achievement of student learningÂ count coun